Cost‐effectiveness of gallbladder histopathology after cholecystectomy for benign disease. Issue 6 (2nd November 2020) - Lundgren, L.; Henriksson, M.; Andersson, B.; Sandström, P.
Abstract : Background: The prevalence of incidental gallbladder cancer is low when performing cholecystectomy for benign disease. The performance of routine or selective histological examination of the gallbladder is still a subject for discussion. The aim of this study was to assess the cost‐effectiveness of these different approaches. Methods: Four management strategies were evaluated using decision‐analytical modelling: no histology, current selective histology as practised in Sweden, macroscopic selective histology, and routine histology. Healthcare costs and life‐years were estimated for a lifetime perspective and combined into incremental cost‐effectiveness ratios (ICERs) to assess the additional cost of achieving an additional life‐year for each management strategy. Results: In the analysis of the four strategies, current selective histology was ruled out due to a higher ICER compared with macroscopic selective histology, which showed better health outcomes (extended dominance). Comparison of routine histology with macroscopic selective histology resulted in a gain of 12 life‐years and an incremental healthcare cost of approximately €1 000 000 in a cohort of 10 000 patients, yielding an estimated ICER of €76 508. When comparing a macroscopic selective strategy with no histological assessment, 50 life‐years would be saved and the ICER was estimated to be €20 708 in a cohort of 10 000 patients undergoing cholecystectomy. Conclusion: A macroscopic selective strategy appears to be the most cost‐effective approach. Abstract : The objective of this study was to assess the cost‐effectiveness of routine and selective gallbladder histopathology when performing cholecystectomy for benign disease. The most important factor for cost‐effectiveness was found to be the cost and number of histological analyses, due to large numbers of cholecystectomies relative to low prevalence of incidental gallbladder cancer. The model indicated that the macroscopic selective strategy was the most beneficial. longer placements improve outcomes Abstract : Antecedentes: La prevalencia del cancer incidental de vesícula biliar cuando se efectúa una colecistectomía por enfermedad benigna es baja. La realización de un estudio anatomopatológico de rutina o selectivo de la vesícula biliar sigue siendo un tema discutido. El objetivo de este estudio fue valorar el coste‐efectividad de los diferentes enfoques. Métodos: Se evaluaron cuatro estrategias de actuación usando modelos analíticos de decisión: no efectuar estudio histológico, estudio histológico selectivo actual como es la práctica en Suecia, estudio histológico selectivo macroscópico y estudio histológico de rutina. Los costes de la atención sanitaria y los años de vida se estimaron en función de una perspectiva de por vida y se combinaron con las tasas de coste‐efectividad incrementales ( incremental cost‐effectiveness ratios, ICERs) para evaluar el coste adicional de lograr un año de vida adicional para cada estrategia de actuación. Resultados: En los análisis de las cuatro estrategias, se eliminó el estudio histológico selectivo actual debido a una mayor ICER en comparación con el estudio histológico selectivo macroscópico, que mostró mejores resultados de salud. La comparación del estudio histológico de rutina con el estudio histológico selectivo macroscópico dio como resultado una ganancia de 12 años de vida y un coste de atención sanitaria incremental de aproximadamente 1.000.000€ en una cohorte de 10.000 pacientes, lo que correspondía a una ICER estimada de 76.508€. Conclusión: El estudio histológico selectivo macroscópico parece ser la estrategia con mayor coste‐efectividad.